The ZEW ICT survey 2002 to 2015: Measuring the digital transformation in German firms - Irene Bertschek; Jörg Ohnemus; Steffen Viete (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
Modern Information and Communication Technologies (ICT) have been proliferating through the entire business sector over recent decades. This increasing digitalization is having a substantial impact on economic activity and is continuously changing the nature of production processes and our day-to-day working life. Since 2002, the ICT Survey carried out by the Centre for European Economic Research (ZEW) has tracked the diffusion and use of ICT in different industries within the German economy. Further surveys were conducted at irregular intervals in 2004, 2007, 2010 and 2015. The survey was designed by ZEW's Research Department Information and Communication Technologies. The data was collected via computer-assisted telephone interviews (CATI) by infas Institute for Applied Social Sciences. The central aim of the survey is twofold: Firstly, a representative picture of the use of ICT by German firms is obtained. Secondly, taking account of a large set of further firm characteristics it should allow an analysis of the consequences of employing ICT and ICT-related projects with respect to different measures of firm performance.
urn:nbn:de:bsz:180-madoc-432257
Keywords: 330